Personality traits and their effects in patients with hemifacial spasm - Jeong-A Lee; Yun Kyung Han; Won Je Jung; Byung H. Lee; Seunghoon Lee (Scientific Reports)
Abstract This study aimed to investigate the personality traits of patients with hemifacial spasm (HFS) and their effects on depression, anxiety, social phobia, and quality of life (QoL). This was a prospective cross-sectional study. Fifty patients diagnosed with HFS and 50 age-, sex-, and education-matched healthy controls (HCs) were enrolled between June and September 2023. Personality traits were assessed using the Korean version of the 50-item International Personality Item Pool (IPIP) representation of Goldberg markers for the Big-Five factor structure. In terms of personality traits, patients with HFS showed lower extraversion and higher neuroticism than HCs. HFS patients also had higher levels of depression, anxiety, and social phobia, as well as lower QoL, than HCs. In patients with HFS, neuroticism decreased with age and was higher in patients with less severe spasms compared to patients with the most severe spasms. Higher extraversion was associated with lower depression and social phobia, and higher QoL. Higher neuroticism was associated with higher depression, anxiety, social interaction anxiety and social phobia, and lower QoL. Understanding these results will not only be helpful in understanding the disease and patients, but it could also be used to establish personalized management strategies.